Determinants of Wedding Consumption in Indonesia - Nisa, Anida Amirilia; Rumayya, Rumayya (Jurnal Ilmu Ekonomi Terapan, 2021)
Marriage unites man and woman in a sacred bond to which economic theories may apply. The economics of marriage includes the analysis of household formation and break up, as well as production and distribution decisions within the household. Marriage usually involves the arrangement of wedding ceremony. Nonetheless, consumption spending on wedding ceremony may differ for each household, depending on their personal preferences. On that account, this study aims to examine the determinants of wedding consumption in Indonesia, which include household income, age, sex, educational attainment, area of residence, and financial literacy level of the household head. This study uses regression method to analyze expenditure data from the National Socio-Economic Survey (Susenas) in 2016. Our findings show that income, age, sex, education, and financial literacy have a significant effect on wedding consumption. This finding has important implications for governments to support the effort to improve financial literacy, especially among couples who are interested in marriage Keywords: Wedding Reception and Ceremonies Expenditures, Marriage Economics, Financial Literacy.JEL: D140, G390, G290